Analisis Kinerja Pengelolaan Keuangan Dana Desa Berdasarkan Rasio ‎Efektivitas dan Rasio Pertumbuhan Pada Kantor Desa Limbur Merangin ‎Kabupaten Merangin - Nur Asiah; Addiarrahman; Muthmainnah (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
This study aims to find out how Village Fund Finance is managed, to find out the factors that influence the effectiveness of Village Fund financial management, to find out how to manage Village Funds more effectively and to find out how well the financial performance of the Limbur Merangin Village Fund is, Merangin Regency. The type of research used is a type of qualitative and quantitative research (mixed method). Quantitative research because the data collected is in the form of figures from the financial reports of the Village Fund Allocation (ADD) on the Village Revenue and Expenditure Budget (APBDesa), while qualitative research is the process of inductively thinking processes related to the dynamics of the relationship between observed phenomena, and always use scientific logic. The results of the study show that in general the financial performance of the Limbur Merangin Village Government of Merangin Regency has been good in managing the finances of the Village Fund Budget. Where is the effectiveness ratio of the Limbur Merangin Village Fund during 2017-2022 in the effective category. This shows that the ability of the Limbur Merangin Village government to achieve the Village Fund target has been going well. The income growth ratio, the Village Fund's income growth fluctuates every year so that the financial performance of the Limbur Merangin Village government is not good in terms of managing the growth ratio.